Computational and experimental biomedical sciences : methods and applications ; ICCEBS 2013–International Conference on Computational and Experimental Biomedical Sciences /: methods and applications ; ICCEBS 2013–International Conference on Computational and Experimental Biomedical Sciences. ([2015]) - Unknown
No abstract available